2010
DOI: 10.1051/fruits/2010013
|View full text |Cite
|
Sign up to set email alerts
|

Fruit quality of Granny Smith apples picked at different harvest times and treated with 1-MCP

Abstract: -Introduction. Superficial scald is one of the most economically serious postharvest disorders of apples. The optimal harvest window and 1-MCP treatment significantly diminish the risk of storage scald and retain quality of apples stored in a normal atmosphere. Materials and methods. Fruits from three different harvest dates (23rd and 30th September, and 7th October 2008) were treated with 1-MCP (SmartFresh TM ) immediately after harvest, and stored in a normal atmosphere (1 ± 0.5)°C for 180 days followed by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…We studied the physical properties of pomelos, including fruit size, weight, volume and apparent density along with the textural properties of the fruit and rind, given that 1 Alice White Green, The nutritional value of pomelo, http://EzineArticles.com/ 5647080, consulted on 11 August 2011. 2 Thai Customs Department, Import-Export Statistics, http://www.customs.go.th/Statistic/StatisticResult2550.jsp?page=1&statType =export&month=12&year=2010&product-CodeCheck=Y&productCode=08054000001 &countryCheck=null&country=, consulted on 11 August 2011. they have implications for fruit handling and the design of processing equipment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We studied the physical properties of pomelos, including fruit size, weight, volume and apparent density along with the textural properties of the fruit and rind, given that 1 Alice White Green, The nutritional value of pomelo, http://EzineArticles.com/ 5647080, consulted on 11 August 2011. 2 Thai Customs Department, Import-Export Statistics, http://www.customs.go.th/Statistic/StatisticResult2550.jsp?page=1&statType =export&month=12&year=2010&product-CodeCheck=Y&productCode=08054000001 &countryCheck=null&country=, consulted on 11 August 2011. they have implications for fruit handling and the design of processing equipment.…”
Section: Methodsmentioning
confidence: 99%
“…The fruit flesh is normally consumed rather than processing it into a juice and is renowned for its good flavor and juicy texture. In addition, it was reported that the flesh of pomelo contains important nutrients including vitamin C, para-insulin, potassium, pectin, natural folic acid and chromium 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apple fruit firmness is one of the quality parameters [18] and presents one of the most important criteria for the consumers. The greater firmness of the organic production fruit would be advantageous in the market [5].…”
Section: Analyses Of Weight Firmness and Color Of Fruitsmentioning
confidence: 99%
“…Pulp firmness is an important quality attribute as it has direct implications on storage potential, resistance to decay organisms, mechanical injury and acceptability to consumers [13]. The results showed that the fruit firmness decreased commensurate with the advancement of the storage period ( figure 1); however, the decline was significantly slowed down by the treatments comprising preharvest spray of [GA 3 + Ca EDTA] + postharvest salicylic acid dip treatment (T9), followed by preharvest spray of [GA 3 + salicylic acid] + postharvest salicylic acid dip (T11).…”
Section: Treatmentmentioning
confidence: 99%